TERAPAN MEDIA PERMAINAN ULAR TANGGA PINTAR DALAM MENINGKATAN MOTIVASI DAN HASIL BELAJAR - Moh. Aniq Kh.B, Ian Bagus Koko Darminto (Universitas PGRI Semarang, 2013)
Use appropriate media often affect the level of motivation and the level of student learning outcomes. Teachers who rarely use the media in the learning process of students' learning motivation and result in low student learning outcomes. The purpose of this study was to determine the increase in learning motivation and learning outcomes through the use of media in a clever snakes and ladders games or thematic integrative learning. Subjects were fourth grade students of SD Negeri 2 Kronggen, totaling 18 students, which consisted of eight male students and 10 female students. The result showed that the students' motivation has increased from 61.11% to pre cycles, 72.22% in the first cycle, while the cycle I 72.22% to 94.44% in the second cycle. Then the student learning outcomes on cognitive aspects showed an increase in pre-cycle condition of the average value of student learning outcomes 68.34 and 61.12% of students learning completeness. While in the first cycle, the average value of student learning outcomes increased to 72.78% and 77.78% mastery learning students. While in the second cycle the average value of student learning outcomes increased to 93.34% and 100% complete learn student. Based on the analysis of research data, it can be concluded that the use of snakes and ladders games or smart media can enhance learning motivation and learning outcomes thematic integrative Elementary School fourth grade students 2 Kronggen